Current Strategic Actions of Russian Manufacturing Subsidiaries of Western Multinational Corporations. Issue 2 (3rd April 2017) - Gurkov, Igor; Saidov, Zokirzhon
ABSTRACT: This article provides a critical analysis of the current strategic actions of Russian manufacturing subsidiaries of Western multinational corporations. The authors retraced the content of strategic actions in various aspects of subsidiary management implemented during 2015–16 and the activities of strategists of different ranks. The authors found that some actions that multinational corporations in Russia implemented during 2014–16 represent standard strategic practices during downturns. In contrast, other strategic practices (facilities expansion against negative market dynamics and reluctance to change the system of permanent job contracts and abundant employee social benefits) generally contradict with the textbook solution for company strategies during downturns.